A regional survey evaluating patient experience seeking trial of labor after cesarean. (12th December 2022) - Davidson, Christina; Walker, Caroline Haley; Sangi-Haghpeykar, Haleh
Abstract: Objective: To evaluate access to trial of labor after cesarean (TOLAC) in a large metropolitan city. Study design: In 2012, a public tertiary care hospital in Houston, TX promoted its TOLAC services on social media, resulting in a surge of self-referrals. In 2018, an electronic survey was distributed by email to 200 women who had previously contacted the hospital regarding TOLAC and posted on 2 local social media TOLAC sites. Women were asked to participate if they ever sought TOLAC in the Houston area. Data were analyzed for trends in patient experience seeking TOLAC and comparisons were made based on number of prior cesarean deliveries (CD) and race/ethnicity. Results: The survey was open for responses for 1 month, with 128 completed surveys by the end of the study time period. Of the respondents, most (64%) had 1 prior CD and identified as White (63%). Most (60%) of all women reported contacting ≥3 providers before finding one that offered TOLAC, with no difference reported for women with 1 vs 2 prior CD ( p = .2). Over half (52%) reported their experience seeking TOLAC to be difficult with more difficulty noted by those with 2 vs 1 prior CD, (61.8% vs 42.7%, ) but not statistically significant ( p = .06). White women were more likely to report an easier experience seeking TOLAC compared to Black women (55.6% vs 30%, p = .04). Overall, 37% attempted TOLAC at the reference hospital. Black (50%) and Hispanic (68.2%) women were significantly more likely to have delivered at the reference hospital than White women (24%) ( p < .05) Conclusion: Our results suggest that women seeking TOLAC have difficulty finding providers who offer the service. This may be especially true for Black and Hispanic women and women with >1 prior CD. Women may utilize social media forums for resources and recommendations and such platforms may represent an underutilized opportunity to identify regional TOLAC services.